Gregory of Nazianzus on the Trinity and the Knowledge of God: In Your Light We Shall See Light. By Christopher A. Beeley - Widdicombe, Peter (The journal of theological studies, 2010)
In this rich and provocative study, Beeley challenges the widely held view that Gregory is an highly apophatic theologian, who makes a distinction between ‘theology’ and ‘economy’. This reflects what Beeley regards as the conventional twentieth-century misreading of the Fathers—that generally modern scholars make a distinction between ‘immanent’ and ‘economic’ modes of thinking about God. This in turn reflects a ruinous failure on the part of patristic scholars and theologians to understand the true nature of theology. The basis of Christian doctrine is ‘the revelatory character’ of theology (p. 201). This was understood by the theologians of the Origenian tradition, a tradition that reaches its culmination with Gregory.